2013
DOI: 10.1016/j.jcis.2013.06.061
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of spinel structured Mn3O4, Co3O4 and Fe3O4 nanoparticles in catalytic oxidation of phenolic contaminants in aqueous solutions

Abstract: Spinel structured Mn3O4, Co3O4 and Fe3O4 nanoparticles were prepared, characterized, and tested in degradation of aqueous phenol in the presence of peroxymonosulfate. It was found that Mn3O4 and Co3O4 nanoparticles are highly effective in heterogeneous activation of peroxymonosulfate to produce sulfate radicals for phenol degradation. The activity shows an order of Mn3O4>Co3O4>Fe3O4. Mn3O4 could fast and completely remove phenol in about 20 min, at the conditions of 25 ppm phenol, 0.4 g/L catalyst, 2 g/L oxone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 191 publications
(73 citation statements)
references
References 42 publications
4
69
0
Order By: Relevance
“…17 Here, we concentrate on doping, since doping is utilized to modify the electronic structure of nanoparticles to achieve improved catalytic, electro-optical, magnetic, chemical, and physical properties. Anandhababu et al 18 4 , where the doping of Fe changes the electronic structure, which in turn affects the conductivity and transferability of the material. Mariammal et al 15 studied the RTFM in Mn-doped CuO nanoflakes induced by oxygen vacancies and surface related defects.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…17 Here, we concentrate on doping, since doping is utilized to modify the electronic structure of nanoparticles to achieve improved catalytic, electro-optical, magnetic, chemical, and physical properties. Anandhababu et al 18 4 , where the doping of Fe changes the electronic structure, which in turn affects the conductivity and transferability of the material. Mariammal et al 15 studied the RTFM in Mn-doped CuO nanoflakes induced by oxygen vacancies and surface related defects.…”
Section: +mentioning
confidence: 99%
“…[1][2][3] The study of magnetic properties of nanosized particles is of great importance from basic as well as applications point of view. Among the various transition metal oxides, Co 3 O 4 is an important p-type semiconductor (direct band gaps at 1.48 and 2.19 eV); widely used as heterogeneous catalyst, 4 anode material in lithium ion batteries, 5 gas sensor, [6][7][8] electrochemical device, 9 solar energy absorber, 10 and magnetic material, 11 where their properties are strongly dependent on their size and morphology. Co 3 O 4 exhibits a normal spinel structure, in which the tetrahedral sites are occupied by Co 2+ and octahedral sites by Co…”
Section: Introductionmentioning
confidence: 99%
“…Due to the unique redox loop (Mn 3+ /Mn 4+ or Mn 2+ /Mn 3+ ) involving a single electron transfer and the superior chemical and physical properties, manganese oxides demonstrate great potentials as catalysts [14]. In our previous studies, manganese oxides at different chemical states showed excellent catalytic abilities for PMS activation [13]. Although fruitful researches have been so far conducted for utilizing various manganese based catalysts for activation of PMS for environmental remediation, few studies focused on the supported manganese oxides catalysis [25].…”
Section: Introductionmentioning
confidence: 94%
“…Sulfate radicals have a higher redox potential than hydroxyl radicals (E 0 = 3.1 V vs. E 0 = 2.7 V) and enable them to be more desirable for persistent organic pollutants (POPs) degradation [11]. Cobalt oxides are proven to be the effective heterogeneous catalysts for PMS activation [12,13]. Nevertheless, due to the metal leaching, employment of cobalt based catalysts would result in the secondary pollution caused by the toxicity of cobalt ions [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that in Mn 3 O 4 , Mn exhibits different oxidation states including divalent Mn 2+ and trivalent Mn 3+ ions located at the tetrahedral and octahedral sites, respectively, which makes it one of the most stable manganese oxide. In addition to its stability, the study of the electrical transport phenomena in Mn 3 O 4 seems so far in demand for various applications such as: lithium-ion batteries (Zhen et al, 2016), supercapacitors (Luo et al, 2016;Xu et al, 2015;Yadav et al, 2016), catalysts and sensors (Saputra et al, 2013;Sharma et al, 2016) because of its low-cost, high natural abundance, great environmental compatibility and good specific capacity. Hausmannite Mn 3 O 4 thin films have been deposited by several techniques such as: the vapor phase growth method (Chang et al, 2005), the pulse laser deposition , the polyol process (Jin et al, 2015), the epitaxy , the hydrothermal method (Dong et al, 2013), the chemical bath deposition (Xu et al, 2006), the chemical successive ionic layer adsorption and reaction (SILAR) process (Gund et al, 2013) and the spray pyrolysis technique (Larbi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%